European Paediatric Surgeons' Association Survey on the Management of Pediatric Appendicitis - Zani, Augusto; Hall, Nigel J.; Rahman, Abidur; Morini, Francesco; Pini Prato, Alessio; Friedmacher, Florian; Koivusalo, Antti; van Heurn, Ernest; Pierro, Agostino (European Journal of Pediatric Surgery, 2019)
Aim To define patterns in the management of pediatric appendicitis.Methods A total of 169 delegates from 42 (24 European) countries completed a validated survey administered at the EUPSA 2017 annual congress.Results In the work-up of children with suspected acute appendicitis, most surgeons rely on full blood count (92%), C-reactive protein (82%), and abdominal ultrasonography (76%), but rarely on computed tomography scans or magnetic resonance imaging. In suspected simple appendicitis, most surgeons (76%) do not perform appendectomy at night in clinically stable patients and start antibiotic preoperatively (64%), but only 15% offer antibiotic therapy alone (no appendectomy). In suspected perforated appendicitis, 96% start antibiotic preoperatively, and 92% perform an appendectomy. Presence of phlegmon/abscess is the main contraindication to immediate surgery. In case of appendix mass, most responders (75%) favor a conservative approach and perform interval appendectomy always (56%) or in selected cases (38%) between 2 and 6 months from the first episode (81%). Children with large intraperitoneal abscesses are managed by percutaneous drainage (59% responders) and by surgery (37% responders). Laparoscopy is the preferred surgical approach for both simple (89%) and perforated appendicitis (81%). Most surgeons send the appendix for histology (96%) and pus for microbiology, if present (78%). At the end of the operation, 58% irrigate the abdominal cavity only if contaminated using saline solution (93%). In selected cases, 52% leave a drain in situ.Conclusion Some aspects of appendicitis management lack consensus, particularly appendix mass and intraperitoneal abscess. Evidence-based guidelines should be developed, which may help standardize care and improve clinical outcomes.
Keywords: appendectomy; perforated; antibiotics; children; pediatric